RESEARCHING UNDER PLATFORMS’ GAZE: RETHINKING THE CHALLENGES OF PLATFORM GOVERNANCE RESEARCH - Are, Carolina (AoIR Selected Papers of Internet Research, 2023)
Researching on platforms through platforms poses challenges to researchers, particularly when observing subcultures and content at the margins. Inspired by Massanari’s essay on researching under the “alt-right” gaze, this paper uses autoethnography to address the impact the system of platform governance has on researcher vulnerability in data collection, persona management and results dissemination, particularly for researchers gathering data censored by platforms and for early-career researchers constructing their personae through digital media. My goal is to examine how the intersection of platform power, academic precarity and the creator economy affects early-career researchers and academics. At the heart of this are the questions: How can researchers gather data, disseminate results and establish a professional profile under platforms’ all-encompassing gaze? What does platform governance and its focus on specific areas of control mean for researching content and users at the margins? What risks do platforms themselves pose to researchers’ work? And how does the broader precarity of particularly early-career academic work intersect with the effects of platform power? To this end, this paper starts with personal experiences of censorship in research to define ‘platform’s gaze’ as gendered, raced, heteronormative and puritan surveillance, constructing a social reality where marginalised individuals and dissent are both hyper-visible and vulnerable to harassment and silencing. It continues by discussing the increasing digital labour required by the ‘impact agenda’ and the difficulty of managing a researcher online persona in an age of growing digital censorship, concluding with considerations on activist interventions in the platform governance field.